2020
DOI: 10.3746/pnf.2020.25.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Starch in Sweet Potato Cultivars Grown in Korea

Abstract: The objective of this study was to investigate the structural and physicochemical properties of starch from seven sweet potato cultivars (Shinyulmi, Sinjami, Hogammi, Jeonmi, Jinyulmi, Juhwangmi, and Pungwonmi). Jeonmi and Jinyulmi had amylose contents of 40.04% and 37.39%, respectively, whereas Juhwangmi and Pungwonmihad amylose contents of 30.95% and 32.37%, respectively. As a result of amylopectin polymerization, the seven cultivars were found to have high (>48%) contents of the degree of polymerization (DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…The same starch particle may have both type of crystallinity (A- and B-type), and it depends upon various factors, for example, cultivation, storage, processing, etc. Seven cultivars of sweet potato (Shinyulmi, Sinjami, Hogammi, Jeonmi, Jinyulmi, Juhwangmi, and Pungwonmi) grown at the National Institute of Crop Science, Rural Development Administration, Muan, Korea, have shown a C A XRD pattern . However, in another study, some white and purple sweet potatoes had shown type C B starches .…”
Section: Resultsmentioning
confidence: 92%
“…The same starch particle may have both type of crystallinity (A- and B-type), and it depends upon various factors, for example, cultivation, storage, processing, etc. Seven cultivars of sweet potato (Shinyulmi, Sinjami, Hogammi, Jeonmi, Jinyulmi, Juhwangmi, and Pungwonmi) grown at the National Institute of Crop Science, Rural Development Administration, Muan, Korea, have shown a C A XRD pattern . However, in another study, some white and purple sweet potatoes had shown type C B starches .…”
Section: Resultsmentioning
confidence: 92%
“…In a general preview, the content of RS in five cultivars of sweet potatoes ranged between 13.2% and 17.2% [23]. However, in a different study carried out in Korea, the RS contents of sweet potato starches ranged from 1.76% in Pungwonmi to 30.75% in Jeonmi [24]; these results were in tandem with the RS content of both yellow sweet potatoes and purple sweet potatoes. For a corn starch sample, a study by Chen et al…”
Section: Content Of Rs In Different Starchy Food Sourcesmentioning
confidence: 99%
“…Cassava (M. esculenta) and sweet potato (I. batatas) are tubers with an important production and distribution worldwide. Both are considered functional foods because they are a source of dietary fiber, vitamin C, thiamin, riboflavin, iron, magnesium, and phosphorus (Zhu, 2015;Kim et al, 2020). Furthermore, M esculenta and I. batatas can complete with corn which is the main source of starch worldwide due to their competitive production costs and both are currently considered as alternative sources of starch for the food industry (Toraya-Avilés et al, 2017;Akintayo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Starch is found in green leaves, seeds, cereals, and tubers and is the main source of energy in the human diet. The starch present in cassava and sweet potato ranges from 17 -25 and 14.6 -25%, respectively (Magallanes-Cruz et al, 2017;Kim et al, 2020). The use of native starch in the food industry is common, however it has limited functional properties, which is why it is modified (Ramos-García et al, 2018).…”
Section: Introductionmentioning
confidence: 99%